The Impact of Cross - Cultural Exchanges on Dual - Cultural Identity: Taking “The Mutual Learning between Chinese Culture and Chinese - Greek Civilizations” as an Example: Taking ‘The Mutual Learning between Chinese Culture and Chinese - Greek Civilizations’ as an Example - Li, Guan Chong; Su, Yuqin; Jiang, Sijia; Zhang, Guodong (Quality in Sport, 2024)
Background: In the context of globalization, cross - cultural communication has become a prominent feature, and , as a symbol of Chinese culture, play an increasingly important role in cross - cultural communication. This study explores the impact of cross - cultural wushu communication on dual cultural identity through the case of Greek students participating in Chinese wushu communication. Methods: The study adopts a qualitative research method, with semi - structured interviews as the main data collection tool. The sample includes 12 Greek students and 2 wushu teachers. The interview data is analyzed using the thematic analysis method. Results: The results show four main themes and eight sub - themes. The strong interest of Greek students in Chinese culture is the main motivation for them to learn wushu. They showed a hard-working spirit during the learning process and overcame numerous difficulties. Wushu cultivation has cultivated students’ self - discipline, perseverance, and respect for etiquette. The contact with wushu cultural elements has enhanced the understanding and comparison of Chinese and Greek cultures and strengthened dual cultural identity. Conclusion: Cross - cultural wushu communication has a positive impact on dual cultural identity and is an important way for skill transmission and cultural understanding and comparison. However, this study also has a small sample size as a limitation. Future studies can expand the sample and further explore this topic.